A educação escolar informal, no romance D. Narcisa de Villar (1859), como instrumento de capacitação intelectual da mulher contra a opressão que ela recebia da família e da sociedade patriarcal brasileira nos séculos XVII e XIX - Silva, Valdísio Vieira da (2022)
This thesis analyzes how the author Ana Luísa de Azevedo Castro, in the novel D. Narcisa de Villar (1859), approaches education as an instrument of tranformatiuon and liberation of women oppressed by the family and the Brazilian patriarchal society. This research project has the general objective: To understanding how informal school education, in the novel D. Narcisa de Villar (1859), works as an instrument for the intellectual empowerment of women against the oppression that they received from the family and from the Brazilian patriarchal society exerted in the 17th and 19th centuries. Initial research on the investigated novel makes it evident that education, as an instrument of personal transformation and liberation, constitutes an object of prolonged and interdisciplinary study. Wu start from this undetstanding, from the undetstanding that we have come to from the significant readings on the novel and on the theoretical and criticalpositions of literatuyre, pedagogy and education, history of western and Brazilian education, philosophy of education, sociology of literature and other areas related and auxiliary to the theme of this thesis. From these assumptions, westart from the understanding that our thesis is to show that: School education, in the novel D. Narcisa de Villar, contributed to transforming consciousness and freeing, personally, socially and politically, women oppressed by family and society Brazilian patriarchy. The analysis of the problem and the objectives that we pursue en this academic work makes it evident that this research will be of a bibliographic and documentary nature. To complete this sense, we base the textual constructicion of this thesis on the theoretical bases presented by the authors: Aranha (2012), Larroyo (1980), Bittar (2009), Pìlette, Pilette (2018), Manacorda (2010), Cambi (1999) and Riboulet (2020, vol. 1, 2, 3 and 4). The conclusion we reached, at the end of the initial bibliographic and documentary research, is that informal school education, in the novel D. Narcisa de Villar, marks two different moments from each other. The first moment is marked by the absence of educational activity in the social space of the big house, contributing to the oppression of women by the family and patriarchal society. The second, due to the presence of education among the servants, leading them to acquire rudiments in Portuguese, the Catholic Christian religion, good Christian customs and the formation of critical self-awareness as a personal, social and political being.